Competency of health workers in detecting and managing gestational hypertension, pre-eclampsia, severe pre-eclampsia and eclampsia during antenatal check-ups in primary care health facilities in Bangladesh: a cross-sectional study. Issue 7 (28th July 2021) - Billah, Sk Masum; Khan, Abdullah Nurus Salam; Rokonuzzaman, S M; Huq, Nafisa Lira; Khan, Marufa Aziz; Priyanka, Sabrina Sharmin; Mannan, Imteaz Ibne; Rahman, Setara; Arifeen, Shams El; George, Joby
Abstract : Study objective: To evaluate the competency of trained health workers in detecting and managing hypertensive disorders of pregnancy during routine antenatal check-ups (ANCs) at primary care facilities in Bangladesh. Study design and settings: Cross-sectional study; conducted in 26 primary care facilities. Outcome measures: Accurate diagnosis of the hypertensive disorders of pregnancy. Method: In total 1560 ANC consultations provided by primary health workers, known as Family Welfare Visitors (FWVs), were observed using a structured checklist between October 2017 and February 2018. All consultations were reassessed by study physicians for validation. Result: Of the 'true' cases of gestational hypertension (n=32), pre-eclampsia (n=29) and severe pre-eclampsia (n=16), only 3%, 7% and 25%, respectively, were correctly diagnosed by FWVs. Per cent agreement for the diagnosed cases of any hypertensive disorders of pregnancy was 9% and kappa statistics was 0.50 (p value 0.0125). For identification of any hypertensive disorders by FWVs, sensitivity and positive predictive values were 14% and 50%, respectively. There was a moderate positive correlation between the blood pressure measurements taken by FWVs and study physicians. Only 27% of those who had 'some protein' in urine were correctly identified by FWVs. Women diagnosed with any of the hypertensive disorders of pregnancy by FWVs were more likely to be counselled on at least one danger sign of pre-eclampsia (severe headache, blurring of vision and upper abdominal pain) than those without any such diagnosis (41% vs 19%, p value 0.008). All four cases of severe pre-eclampsia diagnosed by FWVs were given a loading dose of intramuscular magnesium sulphate and three among them were referred to a higher facility. Conclusion: The FWVs should be appropriately trained on risk assessment of pregnant women with particular emphasis on accurately assessing the diagnostic criteria of hypertensive disorders of pregnancy and its management.